Evaluation of beneficiation constraints for identified critical minerals in Zimbabwe - Denhere, Rumbidzai (My University, 2021)
Firmly anchored on the notion that beneficiation in natural resources could be a driver of structural transformation and global competitiveness for developing countries such as Zimbabwe, this research sought to analyse existing and potential constraints in beneficiating identified critical minerals in Zimbabwe and give recommendations to achieve world level beneficiation. In particular, the study sought to discuss the theoretical and empirical beneficiation concepts, strategies and requirements, conduct literature review on beneficiation highlighting case studies for a few selected government approaches to mineral beneficiation, identify the critical minerals for Zimbabwe mineral industry for beneficiation indicating the available mineral resources for these minerals, identify and evaluate existing and potential beneficiation constraints and finally to provide recommendations on beneficiation constraints so as to be globally competitive for Zimbabwe’s economic growth going forward for the identified critical minerals. The researcher applied both qualitative and quantitative research methods. The research established that considerable success in mineral downstream activities can be achieved using a comprehensive beneficiation strategy that is rooted in a country’s regulatory framework and policies. An enabling environment that is created as a result of good governance, fiscal discipline and robust policy framework, promotes investment in mineral downstream activities. Having a mineral policy that is in sync with a nation’s overall economic development policies was also found to be important for effective implementation and sustaining of downstream activities. For successful beneficiation and value addition to take place, establishment of support structures is imperative, as well as establishment of joint ventures that increase the likelihood of easy access to markets, knowledge, expertise and technology. International trade agreements are also necessary to attract foreign direct investment and also for access to international markets for the finished or semi-finished product. Furthermore, it was established that export bans are not suitable for use by all commodity-dependant developing countries as the success of the strategy is mainly due to the lack of substitutes in the market and such bans on commodities that can easily be substituted in the market place should be avoided. Zimbabwe’s mining industry largely depends on gold, PGMs, diamonds, nickel and chrome as these are the top five contributors to the country’s mineral revenue. Mineral criticality analysis on 32 different publications on critical minerals had REE, PGMs and indium as the three consistently identified critical minerals and lithium with its emerging critical role in the battery technology was also identified as a critical mineral in most of the studies. A survey conducted targeting government parastatal officials (Ministry of Mines, Chamber of Mines and Zimbabwe Mining Development Corporation), beneficiation and mining consultancy experts and mining operations experts had PGMs, gold, diamond and lithium as the critical minerals that Zimbabwe should add value for economic growth and development. The fact that Zimbabwe has the world’s second largest PGMs reserves that are hosted in the Great Dyke, one of the largest lithium reserves hosted in pegmatites in the world and that PGMs and lithium are among critical minerals identified in literature shows that Zimbabwe can focus on these two minerals for beneficiation.From the critical mineral analysis, it was identified that PGMs and lithium are the two key minerals that the country should focus on for beneficiation. Although it was evident that Zimbabwe has made reasonable strides towards PGMs and lithium beneficiation and value addition, constraints exist that impede the production of final products. This was mainly attributed to a lack of investment in the critical minerals’ downstream activities and the country’s political and economic instability that deter foreign investors from participating in the country. This lack of investment has resulted in over-reliance on outdated technology, inadequate power supply, poor transport network system and a generally high cost of doing business. Limited investment in research and development and the absence of smelting and refining infrastructure are also constraints to PGMs and lithium beneficiation. The country should thus focus on beneficiating PGMs and lithium all the way to manufacturing to harness all potential beneficiation benefits, since these were identified as critical minerals and are in abundance in the country, by addressing the identified constraints. Zimbabwe should work on having a comprehensive beneficiation strategy that is supported in the country’s national policies and enacted through regulatory framework. Attracting investments required in transforming its natural endowment into mineral related industries that support lithium and PGMs downstream activities is also of utmost importance. There is need to improve on the investment climate and having a detailed section in the country’s mineral policy that seeks to promote creation of an enabling environment, invest in support structures that include research centres, use of trade agreements and strategic interventions to combat the highlighted constraints
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Engineering, 2021